First Prenatal Diagnosis of a Niemann–Pick Disease Type C2 Revealed by a Cystic Hygroma: A Case Report and Review of the Literature - Ples, Liana; Sima, Romina-Marina; Nedelea, Florina; Moga, Marius (Frontiers in Endocrinology, 2018)
Background: The importance of foetal nuchal translucency (NT) was highlighted in the early 1990s as a useful first-trimester marker to identify foetal chromosomal abnormalities. Here, we report the prenatal diagnosis of a foetus with Niemann–Pick disease type C initially identified by first-trimester ultrasonographic markers and eventually confirmed by extensive genetic evaluation. Case presentation: The foetus of a 30-year-old woman exhibited a cystic hygroma in the first trimester of pregnancy. The woman underwent chorionic villus sampling with extensive genetic investigations to identify the genetic cause of the ultrasonographic findings. Owing to normal karyotype results, further evaluation of 1,024 genes underlying structural abnormalities was performed. This test identified a homozygous mutation of the NPC2 gene (OMIM 601015), which has been reported to be pathogenic and responsible for Niemann–Pick disease type C2. Genetic evaluation of the parents found them to be carriers. Considering the poor prognosis, the parents decided to terminate the pregnancy. Ultrasonographic screening during the subsequent pregnancy showed normal findings; however, molecular testing for the previous familial mutation c.441+1G>A identified the foetus as homozygous for this mutation. Therefore, the parent chose to terminate the subsequent pregnancy as well. Conclusion: We report the first prenatal diagnosis of Niemann–Pick disease type C2 based on a cystic hygroma found during the first trimester of pregnancy as the sole indicator.